2021
DOI: 10.1590/1516-4446-2020-1099
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for eating disorders: an umbrella review of published meta-analyses

Abstract: Objective: To grade the evidence about risk factors for eating disorders (anorexia nervosa, bulimia nervosa, and binge eating disorder) with an umbrella review approach. Methods: This was a systematic review of observational studies on risk factors for eating disorders published in PubMed/PsycInfo/Embase until December 11th, 2019. We recalculated random-effect meta-analyses, heterogeneity, small-study effect, excess significance bias and 95% prediction intervals, grading significant evidence (p o 0.05) from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 76 publications
(118 reference statements)
4
63
1
3
Order By: Relevance
“…Bullying or appearance-related teasing experiences as well as physical or sexual abuse events may promote emotional abuse. These findings confirm the importance to evaluate childhood emotional abuse when assessing CM in people with BN or with BED, despite sexual abuse has been longitudinally recognized as the unique risk factor for EDs [2] and despite literature highlighting the association of physical and sexual abuse with EDs [3]. In this line, emotional abuse was found to be the only CM type directly associated to ED psychopathology, without any effect of psychiatry comorbidity [40] and previous studies suggested that different types of CM do not have the same impact on ED symptoms [41,42].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Bullying or appearance-related teasing experiences as well as physical or sexual abuse events may promote emotional abuse. These findings confirm the importance to evaluate childhood emotional abuse when assessing CM in people with BN or with BED, despite sexual abuse has been longitudinally recognized as the unique risk factor for EDs [2] and despite literature highlighting the association of physical and sexual abuse with EDs [3]. In this line, emotional abuse was found to be the only CM type directly associated to ED psychopathology, without any effect of psychiatry comorbidity [40] and previous studies suggested that different types of CM do not have the same impact on ED symptoms [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…Sociodemographic and clinical data were collected as part of the routine assessment of patients with EDs. Participants in the study were asked to complete the following questionnaires before entering specific treatment programs: (1) the Eating Disorders Inventory-2 (EDI-2) [27]; (2) the Childhood Trauma Questionnaire (CTQ) [28].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, some gaps in the literature need to be noted: few studies investigated substance and alcohol abuse as risk factor for AN as well as young patients at the onset of their illness; still, to the authors' knowledge, very few studies focused on both familial and environmental risk factors. Moreover, Solmi et al, (2020) with an umbrella review accounted for a lack of well-established risk factors for EDs; in fact, even considering several risk factors (e.g., childhood sexual abuse, physical abuse, substance use, impulsivity), strong evidence was not found for any ED, particularly AN [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bullying or appearancerelated teasing experiences as well as physical or sexual abuse events may promote emotional abuse. These ndings con rm the importance to evaluate childhood emotional abuse when assessing CM in people with BN or with BED, despite sexual abuse has been longitudinally recognized as the unique risk factor for EDs [2] and despite literature highlighting the association of physical and sexual abuse with EDs [3]. In this line, emotional abuse was found to be the only CM type directly associated to ED psychopathology, without any effect of psychiatry comorbidity [40] and previous studies suggested that different types of CM do not have the same impact on ED symptoms [41; 42].…”
Section: Discussionmentioning
confidence: 63%
“…Eating Disorders (EDs) are complex psychiatric illnesses likely originating by the interplay of psychosocial, biological and genetic factors [1]. A recent umbrella review [2] assessing longitudinal data on pathogenetic risk factors showed that, among psychosocial factors, childhood sexual abuse and appearance-related teasing victimization are the factors more signi cantly associated with bulimia nervosa (BN) and any type of ED respectively. Literature cross-sectional studies have con rmed that childhood maltreatment (CM) experiences are associated with EDs.…”
Section: Introductionmentioning
confidence: 99%